Resources, environment and development in Bangladesh : with particular reference to the Ganges, Brahmaputra and Meghna basins - Ahmed, Nilufar, ed.; Rasheed, K. B. Sajjadur, ed. (Dhaka : Academic Publishers, 1994)
Environment Management
Keywords: National resources; Environmental development; Ganges basin; Brahmaputra basin; Meghna basin; Socio-economic condition; Land; Agriculture; Forest; Water; Energy